Seasonal influenza surveillance and vaccination policies in the WHO South-East Asian Region - Md Zakiul Hassan; Saleh Haider (BMJ Global Health)
The WHO South-East Asia Region (SEAR), with its high population density, is recognised by epidemiologists as a critical reservoir for the emergence and global dissemination of novel influenza strains, making it a potential epicentre for future influenza pandemics. Despite this significant risk, most SEAR countries lack comprehensive seasonal influenza vaccination policies, resulting in low vaccine uptake across the region. This review analysed the latest WHO National Influenza Programme factsheets from the 11 SEAR member states and supplemented this with extensive manual literature searches using electronic databases and government websites. As of October 2022, only three countries—India, Bhutan and Thailand—had established seasonal influenza vaccination policies. Among them, Bhutan and Thailand have policies that cover all five WHO-recommended high-risk groups. While national influenza surveillance systems are in place across SEAR, only India and the Democratic People’s Republic of Korea claim full population coverage. Influenza vaccine production capacity is limited to Bangladesh, India and Indonesia. The region’s varied climatic conditions and insufficient local data have further obscured the true burden of influenza. Thailand offers a successful model for other countries in the region, beginning with the most vulnerable groups and gradually expanding coverage. To effectively develop and implement national influenza vaccination policies, SEAR countries must close the evidence gap by strengthening surveillance systems to provide accurate, timely data and prioritise context-specific research, leverage existing vaccine infrastructure, enhance public education and finally engage with local and international stakeholders to establish strong international cooperation to support these efforts and improve pandemic preparedness.